Natriuretic peptide receptor 3 (NPR3) is regulated by microRNA-100. (May 2015) - Wong, Lee Lee; Wee, Abby S.Y.; Lim, Jia Yuen; Ng, Jessica Y.X.; Chong, Jenny P.C.; Liew, Oi Wah; Lilyanna, Shera; Martinez, Eliana C.; Ackers-Johnson, Matthew Andrew; Vardy, Leah A.; Armugam, Arunmozhiarasi; Jeyaseelan, Kandiah; et al.
Abstract: Natriuretic peptide receptor 3 (NPR3) is the clearance receptor for the cardiac natriuretic peptides (NPs). By modulating the level of NPs, NPR3 plays an important role in cardiovascular homeostasis. Although the physiological functions of NPR3 have been explored, little is known about its regulation in health or disease. MicroRNAs play an essential role in the post-transcriptional expression of many genes. Our aim was to investigate potential microRNA-based regulation of NPR3 in multiple models. Hypoxic challenge elevated levels of NPPB and ADM mRNA, as well as NT-proBNP and MR-proADM in human left ventricle derived cardiac cells (HCMa), and in the corresponding conditioned medium, as revealed by qRT-PCR and ELISA. NPR3 was decreased while NPR1 was increased by hypoxia at mRNA and protein levels in HCMa. Down-regulation of NPR3 mRNA was also observed in infarct and peri-infarct cardiac tissue from rats undergoing myocardial infarction. From microRNA microarray analyses and microRNA target predictive databases, miR-100 was selected as a candidate regulator of NPR3 expression. Further analyses confirmed up-regulation of miR-100 in hypoxic cells and associated conditioned media. Antagomir-based silencing of miR-100 enhanced NPR3 expression in HCMa. Furthermore, miR-100 levels were markedly up-regulated in rat hearts and in peripheral blood after myocardial infarction and in the blood from heart failure patients. Results from this study point to a role for miR-100 in the regulation of NPR3 expression, and suggest a possible therapeutic target for modulation of NP bioactivity in heart disease. Highlights: We demonstrate a regulatory effect of miR-100 on the expression of NPR3. NPR3 down-regulation by miR-100 may be a compensatory mechanism by increasing NPs. NPR3 is down-regulated in hypoxic challenge with elevated levels of miR-100. Reporter assay indicated direct inhibition of NPR3 expression by miR-100. Elevated miR-100 in cohort with failure predominantly of ischemic etiology